Genetics of Halophilic Microorganisms - Montalvo-Rodríguez, Rafael; Maupin-Furlow, Julie A. (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Halophilic microorganisms are found in all domains of life and thrive in hypersaline (high salt content) environments. These unusual microbes have been a subject of study for many years due to their interesting properties and physiology. Studies of the genetics of halophilic microorganisms (from gene expression and regulation to genomics) have provided understanding into the mechanisms of how life can exist at high salinity levels. Here, we highlight recent studies that advance the knowledge of biological function through examination of the genetics of halophilic microorganisms and their viruses.